Percentage of contribution of tactics and remis strategy in the achievement level ofeEpee - Singapore Youth Olympics 2010 - Samy, A.-S. (World Journal of Sport Sciences, 2010)
Fencing tactics depend on complex movements containing skills of stimulating the opponent's responses and trying to deal with these responses according to fencing distance and timing. The current research aims at identifying the most commonly used tactics and its percentages of contribution during Singapore Youth Olympics 2010. The researcher used the descriptive approach on a sample of 48 matches. Results showed that the percentage of contribution of tactics and remis in results of analyzed matches were 54.76% for the 1st round, 65.61% for the 2nd round, 79.21% for the 3rd round, 90.25% for semi-finals and 100% for the finals.